POWP (CIPEEX, 2025)
Based on the analysis conducted, a significant difficulty in business management was identified among small and micro-enterprises, particularly for Individual Microentrepreneurs (MEIs). It was in this context that the idea for Powp emerged. Powp is an ERP system designed to meet the specific needs of these businesses, providing a comprehensive solution for managing all aspects of business operations. The studies conducted revealed that the initial target audience consists of small businesses, micro-enterprises, and MEIs, although the system is accessible to any type of business. Considering the need for a comprehensive solution that supports business evolution, Powp presents an integrated ERP system aimed at enhancing operational efficiency and decision-making. The system will include robust functionalities for financial control, inventory management, sales, purchasing, and human resources, among others. Integration with financial modules and the generation of detailed reports are some of the features that will aid in the efficient administration of businesses. To define the system's structure and functionality, the standard BPMN notation was adopted, allowing for visual representation of workflows and interactions between system activities. Additionally, the agile Scrum methodology was chosen due to its flexibility and focus on incremental deliveries, enabling continuous adjustments based on user feedback. This approach will ensure the ongoing delivery of features aligned with users' actual needs. The goal of this project is to provide a practical and efficient ERP tool for small and micro-enterprises, assisting them in the comprehensive management of their operations and in achieving their business objectives. It is expected that Powp will contribute to improved business management, fostering a more organized and effective administration regardless of the size or complexity of the business. Furthermore, Powp is committed to social responsibility by allocating resources to support initiatives that promote inclusion and development of small businesses and entrepreneurs in underprivileged communities. Thus, Powp aims to not only be a powerful ERP solution but also a positive force in society, promoting sustainable economic growth and business inclusion.
Keywords: Finance; expenses; Powp; Microentrepreneurs